Enhancing Elementary Students' Writing Skills through STAD-Based Cooperative Learning Supported by Wall Magazine Media - RCL, Khadijah Khadijah (Akademika, 2025)
This study aimed to examine teacher and student activities and improve students' writing skills by implementing the cooperative learning model, Student Teams Achievement Division (STAD), assisted by wall magazine media at State Elementary School (SDN) 72 Banda Aceh. This study employed a classroom action research (CAR) design involving 32 third-grade students as participants. Data were collected using teacher activity observation sheets, student activity observation sheets, and writing skill tests. The findings revealed a significant improvement in both teacher and student performance across the two cycles. In Cycle I, teacher activity reached 75% and was categorized as good, but several issues were identified, including limited apperception, insufficient motivation, and a lack of skill in using wall magazine media effectively. After addressing these weaknesses in Cycle II, teacher activity increased to 88% (very good category). Similarly, student activity rose from 70% in Cycle I to 85% in Cycle II. The improvement was attributed to better engagement, clearer instruction using wall magazines, and more effective motivation strategies. Moreover, students' writing skills showed substantial progress, with the average score increasing from 68% in Cycle I to 84% in Cycle II. Enhancements were observed, particularly in aligning content with the given theme and constructing more effective sentences. Overall, the findings indicate that applying the STAD model assisted by wall magazine media can effectively enhance both learning engagement and writing skills among elementary school students. Keywords: Cooperative Type Student Teams Achievement Division, Wall Magazine, Writing Skills